Study on genetic variability of mud crab, Scylla olivacea at east coast of Peninsular Malaysia using random amplified polymorphic DNA (RAPD): a preliminary assessment - Wan Bayani Wan Omar,; Faridah Mohamad,; Ikhwanuddin @ Polity Abdullah,; Mohd Firdaus Zainal Abidin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Scylla olivacea is one of the mud crabs species and become source of economic income especially for local fishermen in Setiu Wetlands. Nevertheless, the genetic variability of this species are still poorly studied and need to be further clarified. Thus, the Random Amplified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR) technique was used to examine the genetic variability among individuals of S. olivacea from Setiu Wetlands, Terengganu. The genomic DNA was extracted from ten samples of mud crab by using DNeasy kit. Twenty reproducible RAPD fragments generated by OPA 08 and OPA 10 with 17 fragments were polymorphic. The percentage of polymorphic bands was 85% indicates that the population of S. olivacea has high level of polymorphism due to low inbreeding factor within a population. High polymorphism of S. olivacea revealed that this species are genetically variable. Further study should be done for a better understanding about variation and also for conservation and management of this species.